If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1(3 + -1x) = 7x + 5 + -2x 2 + (3 * -1 + -1x * -1) = 7x + 5 + -2x 2 + (-3 + 1x) = 7x + 5 + -2x Combine like terms: 2 + -3 = -1 -1 + 1x = 7x + 5 + -2x Reorder the terms: -1 + 1x = 5 + 7x + -2x Combine like terms: 7x + -2x = 5x -1 + 1x = 5 + 5x Solving -1 + 1x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -1 + 1x + -5x = 5 + 5x + -5x Combine like terms: 1x + -5x = -4x -1 + -4x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 -1 + -4x = 5 + 0 -1 + -4x = 5 Add '1' to each side of the equation. -1 + 1 + -4x = 5 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 5 + 1 -4x = 5 + 1 Combine like terms: 5 + 1 = 6 -4x = 6 Divide each side by '-4'. x = -1.5 Simplifying x = -1.5
| 3x/4-2.78=1.75 | | 2x+2(x+5)=58 | | 2-(3-x)=7x+5-2 | | 10x-15=6x+9 | | x-18=-34 | | 2x^2-32x+78=0 | | x-2.71=0.67 | | 4(3x+1)=-20 | | 25c^3-16c=0 | | B=p+3a+2c | | (b-2/15)=1 | | 6x-3x-9+1=5x+7x-3 | | 2+8v=-94 | | x^3+x^2-21x-45=0 | | 0.16x+27=28 | | 3(x+7)=6(x-1)-4 | | P=b+3a+2c | | 7y-3=6y+9 | | x/3-24=81 | | 5-2[5-(6y-2)]= | | -129-[7-8y-5(6y-2)]= | | 5y+7=42 | | 3(5x-7)=15 | | 4(3x+1)=20 | | -6-28=24+2x | | 4x-1=5x-3 | | 4(3x+1)=21 | | .2y+15=0 | | 6x-28=24+2x | | 6(3+9x)=8(x-2) | | -5x+8=33 | | -8x-57=73-3x |